Para que no haga el oso: hacia una reflexión de las prácticas docentes a través del cine (2012)
Since some time ago, animated movies have reached a special place in cinema thanks to superb productions which effectively condense several ingredients that make each lm an enjoyable experience not only for children, but also for the whole family. The merit of the animated films new producers lies in a planning content that allows these filmic expressions to be more than a product designed to entertain; that’s the reason why nowadays they are focused on presenting stories with a surface structure attractive to infants that, simultaneously, propose to other audiences greater plots complexity in order to invite the viewer to find, after a deep audiovisual material analysis, suggestive insights about a wide range of social, economic , political, cultural and even academic matters. This study analyses how this new trend of animation on the big screen has a place in the field of education due to this document will point out how Kung Fu Panda movie by directors Stevenson and Osborne (2001) poses a number of strong criticisms of traditional practices in the school, meanwhile, between the lines, some suggestions are made about what teachers should take into account in their daily practice of this occupation.